Polynomial Energy Decay Rate for the Wave Equation with Kinetic Boundary Condition - Laoubi, K.; Seba, D. (Acta applicandae mathematicae, 2024)
This paper concerns the polynomial decay of the dissipative wave equation subject to Kinetic boundary condition and non-neglected density in the square. After reformulating this problem into an abstract Cauchy problem, we show the existence and uniqueness of the solution. Then, by analyzing a family of eigenvalues of the corresponding operator, we prove that the rate of energy decay decreases in a polynomial way.